Effects of Arbuscular Mycorrhizal Fungi (AMF) on Heavy Metal and Salt Stress - Aydın Atakan; Hülya Özgönen Özkaya; Oktay Erdoğan (Turkish Journal of Agriculture: Food Science and Technology)
The Arbuscular mycorrhizal fungi (AMF) are microorganisms that live symbiotically with plant roots and have many benefits to soil and plants. In this study, some effects of AMF which are known to be soil and plant beneficial, have been evaluated and solution proposals have been put forward against heavy metal and salinity stress in the soil. Salt accumulation and high concentrations of heavy metal in the soil affects negatively the microbial diversity and activity. Removal of salt acumulation and heavy metal from contaminated soil by chemical and physical methods is both very expensive and ineffective. Therefore, AMF are important for alleviating the heavy metal and salt stress in plants. AMF can alter plant physiol¬ogy and root morphology, increase the uptake of nutrients and water from the soil through an extensive hyphal network, decrease the use of chemical fertilizer, interact with other soil microorganisms plant growth promoting, induce of some resistance parameters in the plants and produce the glomalin which develops the properties and structure of soil. AMF are eco-friendly solutions according to traditional methods and the use of suitable plant-fungi combinations increases the chances of success of these applications.